The Mussel Fauna of the Clinch River, Tennessee and Virginia - John M. Bates; Sally D. Dennis (Hello World!, 1978)
Intensive studies of the Clinch River during the years 1972-1975 have documented the persistence of viable mussel populations at several localities within an approximate 35 kilometer reach of the river (Clinch River Miles 189-211). This restricted area represents approximately 7% of the original river habitat which supported mussels. Of 33 sites intensively sampled, the shoals at Kyles Ford, Tennessee, and. Speer's Ferry, Virginia, were the most productive, yielding 33 and 27 species respectively. This does not enumerate subspecies. While this rich fauna closely approximates that recorded by A. E. Ortmann in 1918, the total number of species recorded for the river has significantly decreased. Ortmann's records indicate 57 species; including subspecies this total becomes 71. The authors' records indicate 43 species, 5 of these being post-impoundment invaders of the lower river. Nineteen species thus appear to have been extirpated from the river; this represents one-third of the original species assemblage. It is of especial note that 12 of these extirpated species are of unique Cumberlandian origin; their continued survival in other rivers is tenuous. The authors express concern for the continued survival of this unique faunal assemblage; adverse environmental impingements pose constant threats. Emphasis must be placed on the preservation of habitats that continue to support these unique mussel assemblages; the Clinch River is certainly one of the most important of these.